Advancing age within established Gleason score categories and the risk of prostate cancer‐specific mortality (PCSM) - Russo, Andrea L.; Chen, Ming‐Hui; Aizer, Ayal A.; Hattangadi, Jona A.; D'Amico, Anthony V. (BJU international, 2012)
Study Type – Prognosis (case series) Level of Evidence 4 What's known on the subject? and What does the study add? There is limited data that suggests that men aged >70 years have a higher proportion of Gleason 8–10 prostate cancer than men aged <70 years, as well as a higher risk of PSA recurrence, distant metastases, and disease‐specific death on univariate analysis. The present study shows that older as compared with younger men with Gleason score 6 and 7 prostate cancer have an increased risk of prostate cancer‐specific mortality. This may be due to the presence of occult high‐grade disease and suggests further diagnostic studies, e.g. multiparametric MRI, may be indicated in these men to reduce biopsy sampling error. OBJECTIVE • To determine if advancing age is a risk factor for high‐grade prostate cancer due to occult high‐grade disease in elderly men with Gleason score 6 or 7 prostate cancer. We investigated whether advancing age is associated with the risk of prostate cancer‐specific mortality (PCSM) within established Gleason score categories adjusting for known predictors of PCSM. PATIENTS AND METHODS • Using data from the Surveillance, Epidemiology and End Results database between 1 January 2004 to 31 December 2007, 166 104 men with non‐metastatic prostate cancer were identified and formed the study cohort. • Within established Gleason score categories, Fine and Gray's multivariable competing risk regressions were used to evaluate whether increasing age at diagnosis was significantly associated with an increased risk of PCSM, adjusting for prostate‐specific antigen level and T‐category at diagnosis and whether treatment was curative or non‐curative. RESULTS • After adjusting for treatment and prognostic factors, Gleason score 8–10 and 7 as compared with ≤6 was associated with an increased risk of PCSM (P < 0.001). • Increasing age was associated with an increased risk of PCSM only in Gleason score 6 (adjusted hazard ratio [AHR] 1.06, 95% confidence interval [CI] 1.04–1.08, P < 0.001) and 7 (AHR 1.02, 95% CI 1.01–1.03, P < 0.001), but not with Gleason score 8–10 (AHR 0.999, 95% CI 0.995–1.003, P= 0.61). • These risks were highest in men aged >70 years having Gleason score 6 (AHR 1.10, 95% CI 1.07–1.13, P < 0.001) and Gleason score 7 prostate cancer (AHR 1.04, 95% CI 1.02–1.06, P < 0.001). CONCLUSIONS • PCSM increases with advancing age in men with Gleason score 6 and 7 but not 8–10 prostate cancer. • Techniques to reduce biopsy sampling error in men, particularly those aged >70 years and healthy with Gleason score 6 and 7 disease deserve further study.